Date Palm leaves Fiber Utilization as sorbent for Crude Oil Spill Cleanup and the Temperature Effect - Khairallah, Ihsan Ali; Abass, Zina Abed Al-Ameer; Nasir, Dr. Mohammad Ibrahim (Journal of Petroleum Research and Studies, 2013)
Crude oil spill are a global concern due to the environmental and economic impact as well as harm the beauty of the polluted sites. Date Palm leaves fiber (DPLF) as a natural agricultural fiber, which is environmentally materials, biodegradable, renewable, abundant, and cheap. A hollow cellulosic material like DPLF is a potential sorbent to counter the oil spill pollution. The oil sorption capacity (OSC) of fresh and weathered oils into DPLF as a sorbent was studied. The effects of contact time and temperature on sorption were studied in simulated tap water as well as salty water. The OSC increases with increasing the contact time. The DPLF has given oil sorption capacity of 4.534-7.985 g oil/g sorbent for a contact time of 5-90 min for fresh oil (tap water, at room temperature). This OSC are considered to be good for a sorbent considering it is locally available and not expensive. Fresh oil is having higher OSC at room temperature at all the experimental times (5-120 min). At lower temperature, e.g. 15 °C the adsorption of oil having greater role in increasing OSC, since at low temperature the oil having high viscosity and that will increase the adherence of oil onto the surface of the fibers and within the capillary during drainage. At room temperature and little higher e.g. 25 & 30 °C , the oil will have less viscosity and more diffusion and that will increase the absorption within the internal capillary and lumens of the fibers and that increase the OSC. There is decrease in viscosity at higher temperature e.g. 45 & 60 °C that will increase the diffusion in the oil and increase the segmental mobility of the fibers as well as increasing the penetration of oil into the pores and lumens of the fibers. That will increase the OSC, but much oil will come out during the drainage time (5 min).